Chitosan-tripolyphosphate nanoparticles designed to encapsulate polyphenolic compounds for biomedical and pharmaceutical applications − A review - Di Santo, Mariana Carolina (2021)
Plant-based polyphenols are natural compounds, present in fruits and vegetables. During recent years, polyphenols have gained special attention due to their nutraceutical and pharmacological activities for the prevention and treatment of human diseases. Nevertheless, their photosensitivity and low bioavailability, rapid metabolism and short biological half-life represent the major limitations for their use, which could be overcome by polyphenols encapsulation (flavonoids and non-flavonoids) into chitosan (CS)-tripolyphosphate (TPP) based nanoparticles (NP). In this review, we particularly focused on the ionic gelation method for the NP design. This contribution exhaustively discusses and compares results of scientific reports published in the last decade referring to ionic gelation applied for the protection, controlled and site-directed delivery of polyphenols. As a consequence, CS-TPP NP would constitute true platforms to transport polyphenols, or a combination of them, to be used for the designing of a new generation of drugs or nutraceuticals.